2021
DOI: 10.33085/jdg.v3i2.4746
|View full text |Cite
|
Sign up to set email alerts
|

Konsumsi Pangan dan Densitas Gizi Wanita Dewasa Usia 19-49 Tahun di Indonesia

Abstract: ABSTRAKLatar Belakang; Hidden hunger atau kelaparan tersembunyi ditandai dengan kekurangan zat gizi mikro yaitu vitamin & mineral. Masalah ini menjadi tantangan baru yang harus diselesaikan di Indonesia. Tujuan; untuk menganalisis konsumsi pangan dan densitas gizi penduduk wanita dewasa Indonesia. Metode; dilakukan dengan menganalisis data Survei Konsumsi Makanan Indonesia (SKMI) 2014 yang dikumpulkan menggunakan metode food recall 24 jam. Jumlah subjek sebanyak 31746 wanita dewasa di Indonesia. Kecukupan zat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…This is in line with previous studies which show that consumption of protein, vegetable and fruit sources is still low (4). This study was also in line with previous studies which showed that the density of protein, calcium, vitamin A and vitamin C in adults was still below the recommendation (14,19). The low consumption of vegetables, fruits and animal foods in the adult population in Indonesia was one of the factors that causes the low density of calcium and vitamin intake, especially vitamins A and C.…”
Section: Discussionsupporting
confidence: 91%
“…This is in line with previous studies which show that consumption of protein, vegetable and fruit sources is still low (4). This study was also in line with previous studies which showed that the density of protein, calcium, vitamin A and vitamin C in adults was still below the recommendation (14,19). The low consumption of vegetables, fruits and animal foods in the adult population in Indonesia was one of the factors that causes the low density of calcium and vitamin intake, especially vitamins A and C.…”
Section: Discussionsupporting
confidence: 91%